New generation free trade agreements as a driver of institutional change: A case of Vietnam [version 2; peer review: 2 approved] - Mariusz Boguszewski (Stosunki Międzynarodowe, 2022)
According to new institutional economics, institutional change is a precondition to economic change and is caused by multiple forces. In addition to path dependence, and strategic policy direction of the country, there are external forces which might have a path-breaking effect. This paper investigates the role of new generation free trade agreements (NGFTAs) in the process of institutional change using the case of Vietnam. It focuses on the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) and the EU-Vietnam Free Trade Agreement (EVFTA) as the most advanced trade agreements ever concluded between developed and developing economies. The findings are based on selected new generation provisions of the CPTPP and EVFTA that confirmed limited success in formal institutional change, no visible impact on the informal part of the institutional setting, and a lack of enforcement incentives. However, institutional change might be achieved by market shifts that activate businesses. These entities, for example, enforce intellectual property rights, modern corporate governance standards or labor rights protection that might cause the spill-over effect into a broader spectrum of economic actors. Thus, they might cause a shift in informal norms triggering incremental changes leading to successful institutional change. NGFTAs might be considered indirect facilitators of this process because they promote a friendly business environment and increase Vietnam‘s investment attractiveness.